Enhancing quality of life through physical exercise in a patient with triple lumbar disc herniation: A longitudinal case study - Kristina Randow de Almeida; Marko Kapeleti; Vuk Stevanović; Vladimir Mrdaković; Marija Macura (Exercise and Quality of Life)
Lumbar disc herniation, a growing condition, significantly impacts work productivity, mental health, and quality of life. It alters functional movement patterns and causes improper compensatory body positioning, leading to muscle dysfunction. Physical exercise is a key treatment for chronic cases. This case study examined a 37-year-old male with moderate triple lumbar disc herniation and degenerative disc changes at L3-L4, L4-L5, and L5-S1. The subject followed a 10-week home-based exercise program performed 4 to 5 times weekly for 45 minutes per session. The program consisted of variations of body-weight exercises, supplemented with additional equipment, and progressively increased in intensity and volume, targeting hip joint mobility and strengthening of deep back, abdominal, and thigh muscles. Initial and final assessments included the Pain Detect test, the Short Form Health Survey-36 on quality of life, Manual Muscle Testing (MMT), Functional Movement Screen (FMS), and body composition analysis. Questionnaires indicated significant pain reduction and improvements in physical condition and psychosocial well-being. MMT improved from 4 to 5, FMS from 2 to 3, and body composition showed positive changes: weight (+1.5%), body water (+3.4%), skeletal muscle (+2.8%), and body fat (-6.6%). The subject reported substantial pain reduction, improved physical condition and psychosocial well-being, as well as enhanced muscle strength, functional movement patterns, and body composition. This case study highlights the program’s effectiveness in treating lumbar disc herniation and enhancing quality of life. Additionally, the program is suitable for preventing lumbar disc herniation and improving overall quality of life in the broader population.